Linguistic Picture of the Death of Edvard Benes in the Czech Press - Zabransky, Lukas (Bohemica Olomucensia, 2015)
In the study, the author examined the linguistic picture of the death of President Edvard Benes in important Czech periodicals of that era. In articles thematically related to the death and funeral rites of this distinctive and internationally recognized leader of the Czechoslovak national policy, the author verified some of the methods of cognitive linguistics/language picture of the world. The following aspects were considered to be of the highest importance: conceptual metaphor, framing type/categorization, own opposition vs. opposition of the others. The greatest emphasis was placed on exploring stereotypes and political morality (conservative versus progressive). Before proceeding to the analysis of the linguistic picture of the world of President Benes, the author placed the display of his death into a wider context and summarised the basic characteristics of the linguistic picture of the world of the most distinctive Czechoslovak presidents of the breakthrough stages of political development: T. G. Masaryk, K. Gottwald, G. Husak and Vaclav Havel.
Keywords: presidents; linguistic picture of the world; cognitive linguistics; stereotypes; political morality; blending of spaces; E. Benes; T. G. Masaryk; K. Gottwald; G. Husak; V. Havel